Wideband Patch Antenna with Shorting Vias - Xue Chen; Haipeng Dou (International Journal of Antennas and Propagation)
A novel patch antenna with three resonant modes is proposed for wideband applications. By introducing the ring slot on the circular patch, the TM02 mode of the smaller circular patch and the TM02 mode of the annular ring can be excited. Also, compared with the traditional circular patch with shorting vias, four components of shorting vias are distributed nonuniformly on the edge of the proposed patch antenna, which can generate another new resonance mode. By merging the three resonant modes, the impedance bandwidth of the antenna is expanded. Meanwhile, the gain of the antenna is enhanced in the wide operating band. The results illustrate that the antenna can operate in the 5.8 GHz ISM band. Its −10 dB impedance bandwidth is from 5.06 to 6.99 GHz, and the relative bandwidth reaches 32%. In addition, the maximum gain of 5.3 dBi is obtained at 6.7 GHz.